Oral manifestations in patients with HIV/AIDS: a literature review (Research, Society and Development, 2022)
The immunosuppression due generated in patients affected by the infection of the Human Immunodeficiency Virus (HIV) or the Acquired Immunodeficiency Syndrome (AIDS), there is the presentation of oral manifestations. Therefore, this research aims to identify in the scientific literature the main oral manifestations associated with HIV/AIDS infection and the role of the dentist in the diagnosis of these conditions. For this, an integrative literature review was used, searching the electronic databases Scientific Electronic Library Online and the Virtual Health Library with the intermediation of health descriptors and with a time period from 2013 to 2021. The sample was listed in 3 stages and the results analyzed by descriptive synthesis. A sample of 10 articles was obtained. The analysis showed that oral manifestations are common in individuals with HIV infection and that the most incidents are candidiasis, hairy leukoplakia and Kaposi's sarcoma. Dental surgeons are essential in identifying these oral manifestations that, if identified early, can improve the quality of life of individuals. It is therefore concluded that this is a topic of great relevance to national public health, that oral manifestations are very prevalent in these patients and that dentists must have adequate knowledge to diagnose and treat them.